1993
DOI: 10.1080/02786829308959637
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Prediction of the Performance of a Shrouded Probe Sampling in Turbulent Flow

Abstract: A numerical simulation is presented for the performance of a shrouded probe sampling at a zero yaw angle to a turbulent flow stream. The mean turbulent flow is calculated using the standard K-E turbulence closure model. The trajectories of particles in the flow field are simulated by solving the corresponding Lagrangian equation of particle motion which includes such effects as inertia, drag, gravity, Saffmau force, and turbulent diffusion. Three parameters describing the performance of a sampling probe-aspira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…The principle of operation of a shrouded probe is presented in several studies (McFarland et al 1989;Gong et al 1993;313 Chandra andMcFarland 1995, 1997) and is briefly discussed in the following paragraph.…”
Section: Use Of Shrouded Probes As Sampling Inletsmentioning
confidence: 99%
See 1 more Smart Citation
“…The principle of operation of a shrouded probe is presented in several studies (McFarland et al 1989;Gong et al 1993;313 Chandra andMcFarland 1995, 1997) and is briefly discussed in the following paragraph.…”
Section: Use Of Shrouded Probes As Sampling Inletsmentioning
confidence: 99%
“…To adjust to this reduction in velocity, the air streamlines have to bend outward when entering the shroud. A numerical study by Gong et al (1993) and a streakline analysis by McFarland et al (1989) demonstrated that the streamlines in the outer region of the shroud bend significantly more than those in the core region. There is an inertial enrichment of aerosol in the shroud, but it is concentrated towards the outer edges of the shroud, and that flow is discharged through the probe waistline region.…”
Section: Use Of Shrouded Probes As Sampling Inletsmentioning
confidence: 99%
“…One is the determination of entry efficiency of sampling probe and the improvement of the sampling inlet to reduce the sampling error during anisokinetic sampling (Chung and Ogden 1986). The other is "shrouded probe" (Gong et al 1993;Chandra and McFarland 1997;Twohy 1998;Irshad et al 2004). In the shrouded probe, the shroud automatically adjusts the free stream air velocity to the inner sampling probe air velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Gong et al (1993Gong et al ( , 1996 carried out numerical simulations of a shrouded probe aerosol inlet, which has flow that can be treated in a two-dimensional manner. Hu and McFarland (2007) used CFD simulation to gain valuable insight into the aerosol behavior and the location of particle deposition in a wetted wall bioaerosol sampling cyclone.…”
Section: Introductionmentioning
confidence: 99%